For You? Using TikTok® to Teach Key Content. (September 2022) - Middleton, Stuart
As management educators grapple with the challenges of educating Gen Z cohorts (born 1997–2015) in and beyond an online COVID-19 environment, social media platforms represent potential teaching tools. TikTok ® is one of the most popular global social media technologies with people aged under 25 and therefore has strong appeal for students. TikTok allows users to view and create short video content of 3 minutes or less for a range of purposes, including education. This review details how TikTok was used to complement other teaching approaches in an undergraduate Strategic Management course. The educational characteristics of TikTok are outlined, including its advantages and disadvantages as a management education tool.